Are unilateral and bilateral knee osteoarthritis patients unique subsets of knee osteoarthritis? A biomechanical perspective. Issue 5 (May 2016) - Messier, S.P.; Beavers, D.P.; Herman, C.; Hunter, D.J.; DeVita, P.
Summary: Objective: To compare the gait of adults with unilateral and bilateral symptomatic and radiographic knee osteoarthritis (OA) to determine whether these subgroups can be treated similarly in the clinic and when recruiting for randomized clinical trials, and to use these data to generate future hypotheses regarding gait in these subsets of knee OA patients. Methods: Cross-sectional investigation of patients with unilateral and bilateral knee OA on gait mechanics using 136 older adults (age ≥55 yrs; 27 kg m −2 ≥ BMI ≤ 41 kg m −2 ; 82% female) with radiographic knee OA. Comparisons were made between the most affected side of the bilateral group (Bi) and the affected side of the unilateral group (Uni), and between symmetry indices of each group. Results: There were no significant differences in any temporal, kinematic, or kinetic measures between the Uni and Bi cohorts. Comparison of symmetry indices between groups also revealed no significant differences. Conclusion: The similarity in lower extremity mechanics between unilateral and bilateral knee OA patients is sufficiently robust to consider both subsets as a single cohort. We hypothesize that biomechanical adaptations to knee OA are at least partially systemic in origin and not based solely on the physiological characteristics of an affected knee joint.